DETERMINANT OF UNWANTED PREGNANCY IN INDONESIA 2017 (A SECONDARY DATA ANALYSIS OF 2017 IDHS) - Essi Guspaneza; Evi Martha (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: The unwanted pregnancy will cause some problems, not only increasing the population but also affecting reproductive health among woman. The unwanted pregnancy can cause miscarriage or abortion, obstructed labour, bleeding and maternal mortality. Based on 2017 Indonesian Demographic and Health Survey (IDHS), the prevalence of unwanted pregnancy is 14% from total pregnancy. This number is increasing compare with Riskesdas in 2013 there was 5.8% unwanted pregnancy. This study aims to examine the determinant of unwanted pregnancy in Indonesia. Methods: This study was a cross sectional design used secondary data analysis of 2017 IDHS. The sample of this study was woman who had aged 15-49 years old and had been pregnant in (…). Totally, 1,997 respondents were recruited in this study. The data was analyzed in univariate and bivariate analysis used Chi-square. Logistic regression analysis was used to analyzed in multivariate. Results: The prevalence of woman who had unwanted pregnancy was 12.8% from total pregnancy. Bivariate analysis showed aged less than 20 years old and more than 35 years old, lived in rural area and had more than 3 children associated with having unwanted pregnancy. Multivariate analysis showed that respondents who had age less than 20 and more than 35 years old (p=0.0001; OR= 1.826) more likely had unwanted pregnancy. Conclusion: This study showed that woman who had risky reproductive aged, lived in rural area and had children more than 3 were statistically significant with unwanted pregnancy. The risky reproductive aged was the most influenced factor for having unwanted pregnancy. So that, the government must support the National Population and Family Planning Board to promote the use of contraceptive among woman in reproductive aged especially in the risky reproductive aged.